Symbolism and ritual around the potatoes in the Andean - Sanchez Garrafa, Rodolfo (2011)
The author of this article considered that a thorough understanding of the ritual reference to crops of corn and potato requires joint examination of the peculiarities of the production system, in each case, with the way the Andean world was built and carried out their social practice. Mythology and ritual associated with corn and potato, are complementary and equally important to explain the holistic view of the Andean man. We have to understand the Mother Potato or «Ispall Mama» as an entity that emerges from the underworld, animated in a «Tinku» with the contribution of the stellar universe.